Motor expertise modulates cortical activation during imagery of simple and complex actions - Jie Yin; Ke Yang; Chendi Zhou; Junhua Dang (Proceedings of the National Academy of Sciences, 2025)
Motor imagery (MI) engages neural systems that overlap with actual movement and is widely used in sport and rehabilitation. Yet conflicting findings suggest that experts show either reduced (neural efficiency) or increased (vivid simulation) brain activation during MI. We hypothesized that task complexity moderates this effect. Using fNIRS, we compared experts and novices during MI of simple versus complex soccer actions. Experts showed lower activation for simple tasks but higher activation for complex ones, while novices showed the opposite pattern. These findings unify opposing accounts of expertise, revealing that expert brains adaptively scale simulation to task demands. This has practical implications for optimizing MI-based training across skill levels.